Sistem Pakar Klasifikasi Siswa Tunagrahita Pada SLB Shanti Yoga Klaten Menggunakan Metode Naive Bayes - Rousyati Universitas BSI PSDKU bandung; Noor Hasan Universitas BSI PSDKU Yogyakarta (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2018)
Abstract - SLB Shanti Yoga is one of the schools with special needs for the mentally retarded in Klaten. The teachers at the school experienced problems in classifying mentally retarded students to determine the class to be occupied. In determining the class adjusted to the mental retardation classification which consists of three levels, namely mild mental retardation, moderate intellectual disability, and severe mental retardation. To determine the level of mental retardation classification in students requires a diagnosis from an expert who is a psychologist and psychiatrist. But the Shanti Yoga Special School does not provide experts. Based on these problems, the authors make the title of the thesis